Text and Language - Arif, Mohsan (Humanities Journal of University of Zakho, 2015)
Generally, this research is an attempt to identify some semantic and stable relations between Text and Language, weather the written language is an obstacle for the text in delivering the message as clear and understandable as the spoken language. Because using language and working on the language in literature framework, such as a poetry verse, is a necessity. Each creative art piece is considered as important event in this language’s lifetime. Therefore, the creative poem reformulates the language in different ways, and creates new vocabularies and new contexts. Entitled as "Text and Language", this research attempts to reform the background theories of Linguistic Analysis on daily language standards, linguistics, and literary language.